USING THE COOPERATIVE LEARNING STRATEGY ON COMPARATIVE DEGREE OF THE FIFTH GRADERS AT FATHONA ISLAMIC SCHOOL PALEMBANG - Kusumah, Yohana Cahya; Firdaus, Masagus (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT The low level of elementary school students’ mastery of English grammatical structures, particularly comparative degrees, indicates the need for the implementation of more interactive and student-centered learning strategies. This study aims to examine the effectiveness of cooperative learning strategies in improving students’ understanding of comparative degrees among fifth-grade students at Fathona Islamic School Palembang. The study employed a quasi-experimental design using a pre-test and post-test non-equivalent control group model, involving 30 students who were divided into an experimental group and a control group. The experimental group received instruction through cooperative learning strategies, while the control group was taught using conventional teaching methods. The results of the analysis showed that the average post-test score of the experimental group (85.4) was higher than that of the control group (72.8). An independent samples t-test confirmed a statistically significant difference between the two groups (p < 0.05). In addition to improving learning outcomes, cooperative learning was also found to enhance students’ active engagement in discussions and group work. These findings conclude that cooperative learning strategies are effective in improving students’ understanding of comparative degrees while also strengthening motivation and active participation in English language learning at the elementary school level. ABSTRAK Rendahnya penguasaan siswa sekolah dasar terhadap struktur tata bahasa Inggris, khususnya comparative degree, menunjukkan perlunya penerapan strategi pembelajaran yang lebih interaktif dan berorientasi pada keterlibatan siswa. Penelitian ini bertujuan untuk mengkaji efektivitas strategi pembelajaran kooperatif dalam meningkatkan pemahaman comparative degree pada siswa kelas V di Sekolah Islam Fathona Palembang. Penelitian menggunakan desain quasi-eksperimental dengan model pre-test dan post-test non-equivalent control group, melibatkan 30 siswa yang terbagi ke dalam kelompok eksperimen dan kelompok kontrol. Kelompok eksperimen memperoleh pembelajaran dengan strategi kooperatif, sementara kelompok kontrol diajar menggunakan metode pembelajaran konvensional. Hasil analisis menunjukkan bahwa nilai rata-rata post-test kelompok eksperimen (85,4) lebih tinggi dibandingkan kelompok kontrol (72,8). Uji independent samples t-test mengonfirmasi adanya perbedaan yang signifikan secara statistik antara kedua kelompok (p < 0,05). Selain meningkatkan hasil belajar, pembelajaran kooperatif juga terbukti mendorong keterlibatan aktif siswa dalam diskusi dan kerja kelompok. Temuan ini menyimpulkan bahwa strategi pembelajaran kooperatif efektif dalam meningkatkan pemahaman comparative degree sekaligus memperkuat motivasi dan partisipasi siswa dalam pembelajaran bahasa Inggris di sekolah dasar.